Oncolytic activity of velogenic and lentogenic Newcastle Disease Virus (NDV) on Saos-2 cells in hypoxic condition - Kosni, Nurneqman Nashreq; Shafee, Norazizah; Omar, Abdul Rahman; Suet, Lin Chia (Universiti Putra Malaysia, 2019)
Introduction: The standard treatment of cancer (surgery, chemotherapy, and radiotherapy) has not improved the survival rate of the patients much over the decades. A new alternative treatment known as oncolytic virotherapy has emerged, utilising selective virus to kill cancer cells. Newcastle disease virus (NDV) is one of the viruses studied for its oncolytic properties. Despite extensive studies have been done, the relationship between the oncolytic activities of different pathotypes (velogenic and lentogenic) of NDV in Saos-2, either in normoxic or hypoxic conditions, have yet to be elucidated. Methods: Saos-2 cells grown in normoxic and hypoxic conditions were infected with different pathotypes of NDV. The cells were then analysed with MTT assay as well as flow cytometry and microscopic analyses. Results: It was found that the cell viability reduced to 57% and 75% when velogenic and lentogenic NDV infected the cells, respectively, in both hypoxic and normoxic conditions. Similar observations were obtained when in flow cytometry and morphological analyses. Conclusion: Velogenic NDV showed higher oncolytic activities compared to that of the lentogenic NDV in both hypoxic and normoxic conditions. These findings warrant further investigation of velogenic NDV to be a potential candidate to be used for the treatment of Saos-2 cell in the future.